Religiosidade dos adolescentes de periferia em face de conflitos e violências - Monte, Silas Paulo Procópio do (2011)
The aim of this dissertation is to investigate and analyze the formation of the subjectivity and the religious praxis of the youth, emphasizing main lines: struggles, violence and mediation. The main lines in this dissertation are related to the finding out of youth struggles and violence manifestations, as well as the meaning of the vision of each one involved in, considering the intrafamily relationship and also their peer interactions. The researching locus covered the intrafamily and the peer mutual interactions in the suburbs of Belo Horizonte city and its metropolitan area. Those areas are an environment of high social risk, worsened by the lack of basic social and public political agendas. With the interest of understanding each religious level of the youth, I take to start two possible observations: the nuclear and the monoparental family formation goes through a crises. Consequently, this has corroborated for weakening of the moral principle and value, producing struggles and violence. To understand the religious phenomeno used four shares the works: To know the Psychology of Religio by Anthony Avila and Adolescents in Conflict by Les Parrott. Surveys and interviews with teens and some social actors. Two studies conducted by the CIA, the statistical reports infractions relative the years of 2009 and 2010 the Court of the State of Minas Gerais. Finally, it will be demonstrated whether the lack of understanding and religious praxis among the youths interfere or not directly on the diverse behaviors, transforming them more vulnerable and violent. It is proposed also possibilities to mediate helping efforts through a supporting network, based on the interpretation of the Youth and Child Statute.